Águas do interior: soluções alternativas coletivas na 8ª Regional de Saúde do Paraná - Plein, Ivonete Terezinha Tremea (2024)
Given the issues related to the quantity and quality of water for human consumption, the State of Paraná has seen considerable growth in the drilling of artesian wells and has organized the distribution of water through the so-called Collective Alternative Solution (CAS) in municipalities. In this context, the objective of this thesis is to survey and systematize the data from Vigiagua (National Program for Water Quality Surveillance for Human Consumption) available in Sisagua (Information System for Water Quality Surveillance for Human Consumption), concerning the SAC in the rural area of the 8th Health Regional of Francisco Beltrão. The method consists of different procedures: i) bibliographic analysis to confirm the relevance of the topic and guide the research stages; ii) collection, systematization, and analysis of the data available in Sisagua for the years 2021 and 2022, considering four parameters: turbidity, total coliforms, Escherichia coli, and free residual chlorine; iii) interviews with technicians from the Health Surveillance Secretariat and the Ministry of Health; iv) field data collection through interviews with municipal technicians responsible for Sisagua, CAS users, and well drilling entrepreneurs; v) field visits to monitor water collection processes and to recognize the location and structure of wells; vi) systematization and production of didactic strategies for discussing the topic. The results show that, in the last ten years, there has been a considerable increase in the number of CAS in Paraná (110%) and in the research region (25%). In 2022, there were 611 active CAS in the 8th Regional, serving an estimated population of 33,081 people (8.64% of the population). During this period, municipal health surveillance collected 6,940 samples, of which 32% had turbidity above the recommended level, 69% contained total coliforms, 22% were contaminated with Escherichia coli, and only 3% had free residual chlorine. The data set is alarming when it is observed that there is a reduced practice of water chlorination despite the significant presence of total coliforms and Escherichia coli, corroborating the initial hypothesis that the population mistakenly assumes that water obtained from artesian wells is always of good quality, a condition safeguarded by public authorities. This research demonstrated that there are issues with the quality of the consumed water and that there are obstacles in the management and control structure to reverse the situation, making it essential to clarify and involve the population. Thus, innovatively, it presented results beyond the thesis through seven didactic strategies for civic education and Environmental Education: i) online offering of the course "Learning about Water"; ii) preparation and availability of a Compendium of water-related materials; iii) availability of the database used in the thesis; iv) participation in scientific events; v) publication of scientific articles and book chapters; vi) publication of articles on water in journalistic language; and vii) cultural publication on Geography topics through poetry and photography.